Development of FinTech business in Lithuania: driving factors and future scenarios - Kamilė Taujanskaitė; Jurgita Kuizinaitė (Business, Management and Economics Engineering, 2022)
Purpose – the research aims to find out the main factors that determine the change in the number of FinTech companies in Lithuania and predict the future development of this sector. Research object: FinTech business sector, described as the number of FinTech companies.